Insights into endometrial cancer profiles and its pattern of recurrences: a study from a leading health center in eastern Morocco - Chatbi, Zainab; Ghizlane, Graiti; Ahmed, Mimouni; Hanane, Saadi; Taheri, Hafsa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Endometrial cancer (EC) is a rising gynecological malignancy, particularly in low- and middle-income countries. This study explored the demographic, clinical, and pathological features of women with EC in eastern Morocco. Methods: A retrospective review of 60 cases of histologically confirmed EC was conducted at Mohammed VI University Hospital, Oujda, from January 2016 to January 2024. Data included demographics, clinical symptoms, diagnostics, treatments, and risk factors. Results: The mean age was 56 years, with 80% aged 50-70. Most patients (60%) resided in urban areas, and 90% were nonsedentary housewives. Vaginal bleeding was the main symptom (87%). Early-stage disease (stage I) was predominant (70%), with endometrioid carcinoma accounting for 65% of cases. Tumor grades were 40% grade I, 45% grade II, and 15% grade III, with >50% myometrial invasion in 45%. Risk factors included postmenopausal status (80%), nulliparity (43%), and overweight (46%), while hypertension and diabetes affected 30% and 20%, respectively. Treatment involved total hysterectomy with bilateral salpingo-oophorectomy (45%) or radical hysterectomy (18.3%). Adjuvant therapy was administered to 76.7%, with 11.7% receiving combined chemo-radiotherapy. Based on ESMO-ESGO-ESTRO risk classification, 60% were low-risk, while high-risk cases showed higher recurrence and poorer outcomes. Conclusions: EC in Morocco is often detected at an early stage, predominantly affecting postmenopausal women. Efforts should focus on early diagnosis and customized treatment strategies for high-risk patients to improve outcomes.